Effect of individual working method on healthy lifestyle behaviors health self efficacy in nursing students Hemşirelik öğrencilerinde bireysel çalışma yönteminin sağlıklı yaşam biçimi davranışlarına ve sağlık öz yeterlilik algısı üzerine etkisi - Köksoy Vayısoğlu, Sümbüle; Öncü, Emine (Journal of Human Sciences, 2018)
Introduction: Getting healthy lifestyle behaviors is important for a healthy life. Aim: In this study, we aimed to determine the effect of individual working method (IWM) on health self-efficacy perception and healthy lifestyle behaviors in nursing students. Material and method: This study was carried out in the spring semester of 2015-2016 academic year using semi-experimental designs and pre-test post-test control group pattern on total 158 first year nursing student. The data of the study were collected by the socio-demographic questionnaire and Healthy Lifestyle Behavior Scale II (HLBS-II) and Health Self-Efficacy Perception Scale (HSEP). While the topics covered in the health promotion and development course program are presented with a group narration and question-answer method, in other group the IWM has been applied which provides the opportunity for the students to evaluate their behavior in addition to narrative method (NM). In the analysis of the data, number, percentage, arithmetic mean, chi square test, t test, correlation analysis and Cohen d formula were used, p <0.05 value was accepted as statistically significant. Results: There was no significant change in the mean score of the HLBS-II score of the students in the NM group at the end of the term (p> 0.05), but the mean scores of the students in the IWM group increased (p <0.001). In the NM group, there was a “low change” in physical activity, nutrition, health responsibility sub-dimensions in the HLBS-II scale and “low/ medium change” in all sub-dimensions in the IWM group (p <0.05). In both groups, the lowest point average for both measures belongs to the nutrition sub-dimension. While there was no change in the NM group (p> 0.05) in the health self-efficacy perception, the increase in the IWM group was significant (p <0.05). Conclusion: It is recommended to use interactive training methods such as IWM besides the NM to gain healthy lifestyle behaviors. Extended English summary is in the end of Full Text PDF (TURKISH) file. Özet Giriş: İnsanlara sağlıklı yaşam biçimi davranışlarının kazandırılması sağlıklı bir yaşam için önemlidir. Amaç: Bu çalışmanın amacı, hemşirelik öğrencilerinde bireysel çalışma yönteminin sağlık öz yeterlik algısı ve sağlıklı yaşam biçimi davranışlarına olan etkisini belirlemektir Gereç ve Yöntem: Bu araştırma yarı deneysel tasarımlardan ön test son test kontrol gruplu desen kullanılarak 2015-2016 eğitim öğretim yılı bahar döneminde 158 hemşirelik birinci sınıf öğrencisi ile yürütülmüştür. Araştırmanın verileri sosyodemografik soru formu, “Sağlıklı Yaşam Biçimi Davranışları II Ölçeği” ve “Sağlık Öz Yeterlilik Algısı Ölçeği” ile toplanmıştır. Sağlığı koruma ve geliştirme dersi programında yer alan konular bir gruba “anlatım ve soru-cevap” yöntemi ile sunulurken diğer gruba ek olarak öğrencilerin kendi davranışlarını değerlendirmelerine fırsat sunan “bireysel çalışma yöntemi” uygulanmıştır. Verilerin analizinde yüzde, aritmetik ortalama, ki kare testi, t testleri, korelasyon analizleri ve Cohen d formulü kullanılmış, p<0.05 değeri istatistiksel olarak anlamlı kabul edilmiştir. Bulgular: Dönem sonunda anlatım yöntemi grubundaki öğrencilerin Sağlıklı Yaşam Biçimi Davranışları Ölçeği II toplam puan ortalamasında anlamlı değişim görülmezken (p>0.05), BÇY grubundaki öğrencilerin puan ortalamalarında artış olmuştur (p<0.001). Anlatım yöntemi grubunda Sağlıklı Yaşam Biçimi Davranışları II Ölçeğinde fiziksel aktivite, beslenme, sağlık sorumluluğu alt boyutlarında “düşük düzeyde”, bireysel çalışma grubunda tüm alt boyutlarda “düşük/orta düzeyde” değişim görülmüştür (p<0.05). Her iki grupta en düşük puan ortalaması beslenme alt boyutuna aittir. Sağlık özyeterlik algısında anlatım yöntemi grubunda değişim görülmezken (p>0.05) Bireysel Çalışma Yöntemi grubunda ki artış anlamlıdır (p<0.05). Sonuç: Sağlıklı yaşam biçimi davranışları ve sağlık özyeterlik algısının gelişiminde bireysel çalışma yönteminin anlatım yönteminden daha etkili olduğu belirlenmiştir. Öneriler: Bireylere sağlıklı yaşam biçimi davranışı kazandırmada anlatım yanında bireysel çalışma yöntemi gibi interaktif eğitim yöntemlerinin kullanılması önerilir.